Increasing National Resilience to Hazards and Disasters: The Perspective from the Gulf Coast of Louisiana and Mississippi: Summary of a Workshop - Steve Olson (The National Academies Press, 2011)
Natural disasters are having an increasing effect on the lives of people in the United States and throughout the world. Every decade, property damage caused by natural disasters and hazards doubles or triples in the United States. More than half of the U.S. population lives within 50 miles of a coast, and all Americans are at risk from such hazards as fires, earthquakes, floods, and wind. The year 2010 saw 950 natural catastrophes around the world2014the second highest annual total ever2014with overall losses estimated at 130 billion. The increasing impact of natural disasters and hazards points to increasing importance of resilience, the ability to prepare and plan for, absorb, recover from, or more successfully adapt to actual or potential adverse events, at the individual , local, state, national, and global levels. Assessing National Resilience to Hazards and Disasters reviews the effects of Hurricane Katrina and other natural and human-induced disasters on the Gulf Coast of Louisiana and Mississippi and to learn more about the resilience of those areas to future disasters. Topics explored in the workshop range from insurance, building codes, and critical infrastructure to private-sector issues, public health, nongovernmental organizations and governance. This workshop summary provides a rich foundation of information to help increase the nation's resilience through actionable recommendations and guidance on the best approaches to reduce adverse impacts from hazards and disasters.

Healthy, Resilient, and Sustainable Communities After Disasters: Strategies, Opportunities, and Planning for Recovery - Institute of Medicine
In the devastation that follows a major disaster, there is a need for multiple sectors to unite and devote new resources to support the rebuilding of infrastructure, the provision of health and social services, the restoration of care delivery systems, and other critical recovery needs. In some cases, billions of dollars from public, private and charitable sources are invested to help communities recover. National rhetoric often characterizes these efforts as a \

Civic Engagement and Social Cohesion: Measuring Dimensions of Social Capital to Inform Policy - National Research Council (The National Academies Press, 2014)
People's bonds, associations and networks - as well as the civil, political, and institutional characteristics of the society in which they live - can be powerful drivers affecting the quality of life among a community's, a city's, or a nation's inhabitants and their ability to achieve both individual and societal goals. Civic engagement, social cohesion, and other dimensions of social capital affect social, economic and health outcomes for individuals and communities. Can these be measured, and can federal surveys contribute toward this end? Can this information be collected elsewhere, and if so, how should it be collected? Civic Engagement and Social Cohesion identifies measurement approaches that can lead to improved understanding of civic engagement, social cohesion, and social capital - and their potential role in explaining the functioning of society. With the needs of data users in mind, this report examines conceptual frameworks developed in the literature to determine promising measures and measurement methods for informing public policy discourse. The report identifies working definitions of key terms; advises on the feasibility and specifications of indicators relevant to analyses of social, economic, and health domains; and assesses the strength of the evidence regarding the relationship between these indicators and observed trends in crime, employment, and resilience to shocks such as natural disasters. Civic Engagement and Social Cohesion weighs the relative merits of surveys, administrative records, and non-government data sources, and considers the appropriate role of the federal statistical system. This report makes recommendations to improve the measurement of civic health through population surveys conducted by the government and identifies priority areas for research, development, and implementation.

Opportunities for the Gulf Research Program: Community Resilience and Health: Summary of a Workshop - LeighAnne Olsen; Steve Olson (The National Academies Press, 2015)
There are many connections between human communities and their surrounding environments that influence community resilience and health in the Gulf of Mexico. The impacts of the Deepwater Horizon oil spill on Gulf communities and ecosystems - coupled with the region's preexisting health challenges and environmental stressors - illustrate the need to better understand these connections. In the future, natural and man-made disasters, climate change impacts, and other environmental stressors will present complex challenges to the physical, mental, and social well-being of communities in the Gulf. Understanding the interrelationships among health, ecological, and economic impacts of disasters and other environmental stressors will be crucial to addressing these challenges. Opportunities for the Gulf Research Program: Community Resilience and Health summarizes a Gulf Research Program workshop held on September 22-23, 2014, in New Orleans, Louisiana. The workshop examined opportunities to improve the health, well-being, and resilience of communities in the Gulf region through discussions with about 50 participants with diverse expertise and experience. These discussions identified perceived needs, challenges, and opportunities that align with the Gulf Research Program's mission and goals - particularly its goal to improve understanding of the connections between human health and the environment to support the development of health and resilient Gulf communities. This workshop is expected to lead to the development of additional Program activities and opportunities for the research community.

Building Community Disaster Resilience Through Private-Public Collaboration - National Research Council (The National Academies Press, 2011)
Natural disasters2014including hurricanes, earthquakes, volcanic eruptions, and floods2014caused more than 220,000 deaths worldwide in the first half of 2010 and wreaked havoc on homes, buildings, and the environment. To withstand and recover from natural and human-caused disasters, it is essential that citizens and communities work together to anticipate threats, limit their effects, and rapidly restore functionality after a crisis. Increasing evidence indicates that collaboration between the private and public sectors could improve the ability of a community to prepare for, respond to, and recover from disasters. Several previous National Research Council reports have identified specific examples of the private and public sectors working cooperatively to reduce the effects of a disaster by implementing building codes, retrofitting buildings, improving community education, or issuing extreme-weather warnings. State and federal governments have acknowledged the importance of collaboration between private and public organizations to develop planning for disaster preparedness and response. Despite growing ad hoc experience across the country, there is currently no comprehensive framework to guide private-public collaboration focused on disaster preparedness, response, and recovery. Building Community Disaster Resilience through Private-Public Collaboration assesses the current state of private-public sector collaboration dedicated to strengthening community resilience, identifies gaps in knowledge and practice, and recommends research that could be targeted for investment. Specifically, the book finds that local-level private-public collaboration is essential to the development of community resilience. Sustainable and effective resilience-focused private-public collaboration is dependent on several basic principles that increase communication among all sectors of the community, incorporate flexibility into collaborative networks, and encourage regular reassessment of collaborative missions, goals, and practices.

Social Isolation and Loneliness in Older Adults: Opportunities for the Health Care System - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Social isolation and loneliness are serious yet underappreciated public health risks that affect a significant portion of the older adult population. Approximately one-quarter of community-dwelling Americans aged 65 and older are considered to be socially isolated, and a significant proportion of adults in the United States report feeling lonely. People who are 50 years of age or older are more likely to experience many of the risk factors that can cause or exacerbate social isolation or loneliness, such as living alone, the loss of family or friends, chronic illness, and sensory impairments. Over a life course, social isolation and loneliness may be episodic or chronic, depending upon an individual's circumstances and perceptions. A substantial body of evidence demonstrates that social isolation presents a major risk for premature mortality, comparable to other risk factors such as high blood pressure, smoking, or obesity. As older adults are particularly high-volume and high-frequency users of the health care system, there is an opportunity for health care professionals to identify, prevent, and mitigate the adverse health impacts of social isolation and loneliness in older adults. Social Isolation and Loneliness in Older Adults summarizes the evidence base and explores how social isolation and loneliness affect health and quality of life in adults aged 50 and older, particularly among low income, underserved, and vulnerable populations. This report makes recommendations specifically for clinical settings of health care to identify those who suffer the resultant negative health impacts of social isolation and loneliness and target interventions to improve their social conditions. Social Isolation and Loneliness in Older Adults considers clinical tools and methodologies, better education and training for the health care workforce, and dissemination and implementation that will be important for translating research into practice, especially as the evidence base for effective interventions continues to flourish.

Building and Measuring Community Resilience: Actions for Communities and the Gulf Research Program - National Academies of Sciences, Engineering,; Medicine
The frequency and severity of disasters over the last few decades have presented unprecedented challenges for communities across the United States. In 2005, Hurricane Katrina exposed the complexity and breadth of a deadly combination of existing community stressors, aging infrastructure, and a powerful natural hazard. In many ways, the devastation of Hurricane Katrina was a turning point for understanding and managing disasters, as well as related plan making and policy formulation. It brought the phrase \

Rebuilding the Unity of Health and the Environment: The Greater Houston Metropolitan Area: Workshop Summary - Institute of Medicine (The National Academies Press, 2005)
Houston is struggling with many of the environmental problems that most of the nation's major metropolitan areas are struggling with - transportation, water and air pollution, flooding, and major demographic changes. Therefore, Houston provided an excellent site for a regional meeting on the relationship between environment and health. The purpose of this workshop in Houston was to bring all the stakeholders together - the private and public sector, along with representatives of the diverse communities in Houston - to discuss the impact of the natural, built, and social environments on human health. Rebuilding the Unity of Health and the Environment summarizes the presentations and discussions of this workshop. The lessons one may draw from this meeting's presentations and discussions apply to other regions that are undergoing similar changes and that must also contend, as does Houston, with the legacies of insufficient planning, environmentally deficient planning, or sometimes, no planning at all.

Enhancing Community Resilience through Social Capital and Connectedness: Stronger Together! - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Disasters caused by natural hazards and other large-scale emergencies are devastating communities in the United States. These events harm individuals, families, communities, and the entire country, including its economy and the federal budget. This report identifies applied research topics, information, and expertise that can inform action and opportunities within the natural hazard mitigation and resilience fields with the goal of reducing the immense human and financial toll of disasters.